'That would be dreadful': The ethical, legal, and social challenges of sharing your Alzheimer's disease biomarker and genetic testing results with others. Issue 1 (19th May 2021) - Largent, Emily A; Stites, Shana D; Harkins, Kristin; Karlawish, Jason
Abstract: Several large clinical trials are underway to discover therapies to delay or prevent the onset of dementia caused by Alzheimer's disease (AD). A common feature of these trials is that they are testing therapies in people who do not yet have changes in memory or thinking—that is, who are cognitively unimpaired—but who have a biologically defined risk of developing dementia caused by AD. When these trials eventually succeed, it is reasonable to expect the widespread adoption of biomarker and genetic testing of cognitively unimpaired individuals into clinical practice, as well as treatment prescribed to individuals at heightened risk. Here, we report results from two qualitative studies that sought to understand with whom, why, and how individuals share their AD biomarker and genetic testing results, respectively. We found that sharing is common within the confines of close relationships. However, when sharing outside such relationships, people have multiple concerns, including stigma and discrimination. These concerns highlight the need for additional legal protections and policy changes in anticipation of the coming transformation of AD clinical care.